Metaphoric descriptions of pre- and post-game performance-related experiences in a soccer team during a competitive season - Toivonen, Hanna-Mari; Pounds, Dionne (2013)
The main aim of the present study was to examine performance-related experiences of a youth female soccer team throughout a competitive season. Perceived game importance and expectations about the games were examined as antecedents of emotional experiences of the team. The perceived individual and team performances, outcomes of the games and the team’s post-game emotional experiences were also investigated. Finally, inferences to the team’s emotional climate were made. The participants included 24 female soccer players between the ages of 14 and 18 from a club team in Central Finland. The data were collected, prior to and after each game of the season, using the metaphor self-generation method. In addition, the players rated the perceived game importance, perceived individual performance and perceived team performance on a 10-point scale. Perceived game expectations were assessed through open-ended questions. Results revealed that the fall season was considered significantly more important than the spring season and the team’s experiences differed correspondingly. During the spring, tiredness was more often reported prior to the games, whereas during the fall, the more often reported pre-game emotional experiences were willingness, anxiety and calmness. Interestingly, the home games were perceived as significantly more important than away games, although better outcomes were achieved away. When the expectations were very positive (>80%), the pre-game experiences were also positive (i.e. happy and willing), whereas when the expectations were less positive (<60%), the pre-game experiences were functionally harmful (i.e. tired and quiet). Interestingly, although the team had better outcomes during the fall, sadness and tiredness were the most reported post-game emotional experiences. During the spring, on the other hand, happiness was more often reported after the games, even after the games lost. Overall, the team had a very successful season. This study provides additional support for the use of the metaphor generation method in the assessment of athletes’ experiences related to performance. The results of this study also supported the importance of the primary and secondary appraisal as antecedents of emotions experienced and the bidirectional emotion-performance relationship suggested by the IZOF model.